Astaxanthin stimulates mitochondrial biogenesis in insulin resistant muscle via activation of AMPK pathway. Issue 1 (31st January 2020) - Nishida, Yasuhiro; Nawaz, Allah; Kado, Tomonobu; Takikawa, Akiko; Igarashi, Yoshiko; Onogi, Yasuhiro; Wada, Tsutomu; Sasaoka, Toshiyasu; Yamamoto, Seiji; Sasahara, Masakiyo; Imura, Johji; Tokuyama, Kumpei; et al.
Abstract: Background: Skeletal muscle is mainly responsible for insulin‐stimulated glucose disposal. Dysfunction in skeletal muscle metabolism especially during obesity contributes to the insulin resistance. Astaxanthin (AX), a natural antioxidant, has been shown to ameliorate hepatic insulin resistance in obese mice. However, its effects in skeletal muscle are poorly understood. The current study aimed to investigate the molecular target of AX in ameliorating skeletal muscle insulin resistance. Methods: We fed 6‐week‐old male C57BL/6J mice with normal chow (NC) or NC supplemented with AX (NC+AX) and high‐fat‐diet (HFD) or HFD supplemented with AX for 24 weeks. We determined the effect of AX on various parameters including insulin sensitivity, glucose uptake, inflammation, kinase signaling, gene expression, and mitochondrial function in muscle. We also determined energy metabolism in intact C2C12 cells treated with AX using the Seahorse XFe96 Extracellular Flux Analyzer and assessed the effect of AX on mitochondrial oxidative phosphorylation and mitochondrial biogenesis. Results: AX‐treated HFD mice showed improved metabolic status with significant reduction in blood glucose, serum total triglycerides, and cholesterol ( p < 0.05). AX‐treated HFD mice also showed improved glucose metabolism by enhancing glucose incorporation into peripheral target tissues, such as the skeletal muscle, rather than by suppressing gluconeogenesis in the liver as shown by hyperinsulinemic–euglycemic clamp study. AX activated AMPK in the skeletal muscle of the HFD mice and upregulated the expressions of transcriptional factors and coactivator, thereby inducing mitochondrial remodeling, including increased mitochondrial oxidative phosphorylation component and free fatty acid metabolism. We also assessed the effects of AX on mitochondrial biogenesis in the siRNA‐mediated AMPK‐depleted C2C12 cells and showed that the effect of AX was lost in the genetically AMPK‐depleted C2C12 cells. Collectively, AX treatment (i) significantly ameliorated insulin resistance and glucose intolerance through regulation of AMPK activation in the muscle, (ii) stimulated mitochondrial biogenesis in the muscle, (iii) enhanced exercise tolerance and exercise‐induced fatty acid metabolism, and (iv) exerted antiinflammatory effects via its antioxidant activity in adipose tissue. Conclusions: We concluded that AX treatment stimulated mitochondrial biogenesis and significantly ameliorated insulin resistance through activation of AMPK pathway in the skeletal muscle.